컴퓨터단층촬영의 요오드화 조영제 부작용으로 인한 사망 관련 조영제 비교 분석 - 유성민(Seong-Min Yu), 한동균(Dong-Kyoon Han), 홍주완(Joo-Wan Hong) (방사선기술과학, 2021)
The incidence of adverse reactions to iodide contrast media was found to have increased owing to their increased use in computed tomography, but the exact reasons were unknown. Based on reported iodide contrast media adverse reactions data, it is recommended to the components of iodide contrast media before use to minimize adverse reactions. It was found that the use of iopromide and iomeprol in iodide contrast media resulted in a higher incidences of death and threat of life resulting from adverse reactions than other ingredients. Patients who are administered iodide contrast media containing iopromide and iomeprol during the computed tomography test should be carefully examined by the relevant medical professional, as the significance of gender and age varies from component to component. As multiple iodide contrast agents are available, the use of an appropriate iodide contrast media will reduce the incidence of iodide contrast media adverse reactions.